Optimization of Biomass Delignification by Extrusion and Analysis of Extrudate Characteristics - Delon Konan; Adama Ndao; Ekoun Koffi; Saïd Elkoun; Mathieu Robert; Denis Rodrigue; Kokou Adjallé (Waste, 2025)
Pretreatment of lignocellulosic biomass remains the primary obstacle to the profitable use of this type of biomass in biorefineries. The challenge lies in the recalcitrance of the lignin-carbohydrate complex to pretreatment, especially the difficulty in removing the lignin to access the carbohydrates (cellulose and hemicellulose). This study had two objectives: (i) to investigate the effect of reactive extrusion on lignocellulosic biomass in terms of delignification percentage and the structural characteristics of the resulting extrudates, and (ii) to propose a novel pretreatment approach involving extrusion technology based on the results of the first objective. Two types of biomasses were used: agricultural residue (corn stover) and forest residue (black spruce chips). By optimizing the extrusion conditions via response surface analysis (RSA), the delignification percentages were significantly improved. For corn stover, the delignification yield increased from 2.3% to 27.4%, while increasing from 1% to 25.3% for black spruce chips. The highest percentages were achieved without the use of sodium hydroxide and for temperatures below 65 °C. Furthermore, the optimized extrudates exhibited important structural changes without any formation of p-cresol, furfural, and 5-hydroxymethylfurfural (HMF) (enzymes and microbial growth-inhibiting compounds). Acetic acid however was detected in corn stover extrudate. The structural changes included the disorganization of the most recalcitrant functional groups, reduction of particle sizes, increase of specific surface areas, and the appearance of microscopic roughness on the particles. Analyzing all the data led to propose a new promising approach to the pretreatment of lignocellulosic biomasses. This approach involves combining extrusion and biodelignification with white rot fungi to improve the enzymatic hydrolysis of carbohydrates.